Study of some cooking and eating quality characters on some Egyptian rice genotypes - Nessreen, N. B.; Ammar, A. K.; Ezzat, A. (Acta Agraria Debreceniensis, 2014)
Some Egyptian rice genotypes [i.e. Japonica (Sakha 104), Japonica/Indica (Egyptian hybrid1) and Indica (Giza 182)] were investigated to evaluate the cooking and eating quality characters. High significant differences in grain shape were observed among rice genotypes. Hulling, milling and head rice percentage were higher in Sakha 104 than other rice genotypes, while Indica type (Giza 182) recorded the lowest values in milling and physical characters. No significant differences were found in chemical composition of the three genotypes of rice was recorded, but Giza 182 had the highest protein content. All Egyptian rice genotypes were low in gelatinization temperature and soft in gel consistency. Japonica and Indica rice varieties were low in amylase content, while Japonica/Indica rice variety was intermediate. The use of RVA is considered a good index for palatability evaluation for milled rice flour and starch. The Indica and Japonica/Indica types are low in breakdown viscosity, but higher in cooked pasta than Japonica type. Japonica type recorded the best score in panel test, followed by Indica type, while Indica/Japonica rice variety was the least accepted by Egyptian consumer.